Pendampingan Tata Kelola Pemerintah Desa Berbasis Kearifan Lokal dalam Mendukung Desa Wisata - Suwandoko, Suwandoko; Winanta, Rizza Arge; Hardyati, Desty Puteri (Madani : Indonesian Journal of Civil Society, 2025)
The Polengan Village Government, Srumbung District, Magelang Regency has a problem in organizing tourist villages. The problem is the lack of community participation to support tourist villages. The Polengan Village Government has not been optimal in managing village government governance to support tourist villages. Based on this, assistance was provided for village government governance based on local wisdom in supporting tourist villages in Polengan Village, Srumbung District, Magelang Regency. The activities carried out were the socialization of village institutions in organizing village government, socialization of community participation in formulating tourist village policies in Polengan Village, socialization of village government governance management to support tourist villages, and assistance for village governance based on local wisdom in supporting tourist villages. Community service activities aim to provide knowledge for the village government and the community to implement village government governance by the conditions in Polengan Village. Community service activities also help the Polengan Village government to manage village government based on local wisdom to develop tourist villages in Polengan Village.